Analisis Suseptibilitas Magnetik Batuan Pengeboran di Blok Elang Sumbawa - Romi Aprianto; Kirbani Sri Brtopuspito (Department of Physics Education, Universitas Mataram, 2015)
Magnetic susceptibility measurements have been performed in 6 holes hole (ROM-001, ROM-002, ROM-003, ROM-004, ROM-005, dan ROM-006) in Elang, Sumbawa. This study aimed to determine the correlation between magnetic susceptibility in holes. Magnetic measurements were performed using Suceptibility Meter KT-10. Data processing is done by using software Oasis Montaj Drillhole Plotting to analyze correlations and relationships between holes. The interpretation shows that thereÃ¢â¬â¢s correlation between magnetic susceptibility values with intrusion system of phorphyry Cu-Au. The highest range of magnetic susceptibility value is in Chlorite Sericite Zone (pgm) 0.19x10-3 SI to 1459x10-3 SI. From the magnetic susceptibility values have been estimated position of the intrusion, which is in the ROM 006.